Nuclear genome size and genomic distribution of ribosomal DNA in Musa and Ensete (Musaceae): taxonomic implications - Bartos, J; Alkhimova, O; Dolezelová, M; De Langhe, E; Dolezel, J (Cytogenetic and genome research, 2005)
Nuclear DNA content and genomic distributions of 5S and 45S rDNA were examined in nineteen diploid accessions of the genus Musa representing its four sections Eumusa, Rhodochlamys, Callimusa and Australimusa, and in Ensete gilletii, which was the outgroup in this study. In the Eumusa (x = 11), 2C DNA content ranged from 1.130 to 1.377 pg, M. balbisiana having the lowest DNA content of all sections. M. beccarii (x = 9), a representative of Callimusa, had the highest 2C nuclear DNA content (1.561 pg). Species belonging to Rhodochlamys (x = 11) and Australimusa (x = 10) had 2C DNA contents ranging from 1.191 to 1.299 pg and from 1.435 to 1.547 pg, respectively. E. gilletii (x = 9) had 2C DNA content of 1.210 pg. The number of 5S rDNA loci in Musa varied from 4 to 8 per diploid cell. While different numbers of 5S rDNA loci were observed within Eumusa and Rhodochlamys, four 5S rDNA loci were observed in all accessions of Australimusa. M. beccarii (Callimusa) and E. gilletii contained 5S rRNA gene clusters on five and six chromosomes, respectively. The number of 45S rDNA loci was conserved within individual sections. Hierarchical cluster analysis of genome size, number of chromosomes and 45S rDNA sites suggested a close relationship between Rhodochlamys and Eumusa; Australimusa was clearly separated as were M. beccarii and E. gilletii. Within the Eumusa-Rhodochlamys group, M. balbisiana, M. schizocarpa and M. ornata formed distinct subgroups, clearly separated from the accessions of M. acuminata, M. mannii, M. laterita and M. velutina, which formed a tight subgroup. The results expand the knowledge of genome size and genomic distribution of ribosomal DNA in Musa and Ensete. They aid in clarification of the taxonomical classification of Musa and show a need to supplement the analyses on the DNA sequence level with cytogenetic studies.
Keywords: Musaceae; banánovníkovité; genom rostlinný; buněčné jádro; banánovník; Cell Nucleus; Species Specificity; druhová specificita; Genome, Plant; Geography; RNA, Plant; DNA, Plant; zeměpis; DNA, Ribosomal; Musa; DNA rostlinná; ribozomální DNA; RNA rostlin